Luminescent polymers - Freire Obando, Paul Eduardo (2022)
Polymers are well known and widely used materials that are made of repetitive small molecules called monomer. Their characteristics and properties are particular, depending on the kind of monomers that are bonded and also the way they are linked to each other. Polymer’s presence is very wide in contemporary life, because there is a great variety of them, and one the main classifications of polymers is based on natural and synthetic polymers [1]. On the other side, luminescence is the emission of light waves that produce some bodies when they are at moderate temperatures, then that it is not consequence of heat exposition, that is the reason that kind of light emission is called cold light[2]. The present work is an extensive review of all the phenomena that are associated with the luminescence that some polymers present such as: The review start with de phenomena of luminescence by itself, then the classification of luminescent polymers with several kinds of polymers it is going to be presented. Also it is going to be review the importance of luminescent polymers and their broad range of applications. This includes which kind of polymers have been used in different fields, from the well know organic-emitting light diodes (OLEDS) used in screens for the develop of electronic devices, to applications in energy industries by solar cells, and also in the field of medicine by bioimaging applications[3]. And finally, it will be revised the aggregation induced luminescence or aggregation-induced emission (AIE) and why these phenomena occur in some materials. The objective of this review is to develop a wide and general overview that of the types of luminescent polymers applications, the reasons of the occurring phenomena and also why they can become important in different fields and applications.